Viability of Lucilia sericata maggots after exposure to wound antiseptics. Issue 3 (11th July 2016) - Daeschlein, Georg; Napp, Matthias; Assadian, Ojan; von Podewils, Sebastian; Reese, Kevin; Hinz, Peter; Matiasek, Johannes; Spitzmueller, Romy; Humphreys, Paul; Jünger, Michael; Kramer, Axel
Abstract: After debridement and before dressing a wound with maggots of calliphorid flies, one frequently performed step is the application of antiseptics to the prepared wound bed. However, the concomitant application of antiseptic agents during maggot therapy is regarded controversial as antiseptics may interfere with maggots' viability. In this experimental in vitro study, the viability of fly maggots was investigated after exposure to various antiseptics frequently used in wound care. Here, we show that Lucilia sericata fly maggots can survive up to an hour's exposure to wound antiseptics such as octenidine, povidone‐iodine or polihexanide. Concomitant short‐term application of wound antiseptics together with maggots on wound beds is tolerated by larvae and does not impair their viability.